Anti-diabetes and Anti-obesity Medicinal Plants and Phytochemicals Safety, Efficacy, and Action Mechanisms - Saad, Bashar; Zaid, Hilal; Shanak, Siba.; Kadan, Sleman; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This work presents a systematic review of traditional herbal medicine and their active compounds, as well as their mechanism of action in the prevention and treatment of diabetes and obesity. The side effects and safety of herbal-derived anti-diabetic and anti-obesity phytochemicals are detailed in depth, and the text has a strong focus on current and future trends in anti-diabetic medicinal plants. This unique and comprehensive text is the only current book on the market focusing exclusively on medicinal plants used to combat obesity and diabetes. An introductory chapter focuses on diabetes and obesity and introduces the major causes and main treatments of this increasing epidemic in modern society. Readers are then introduced to medicinal plants, including details on their therapeutic aspects, plus side effects and safety. Following chapters focus on anti-diabetic and anti-obesity medicinal plants, as well as phytogenic natural products in the treatment of each. The text closes by focusing on present and future trends and challenges in these medicinal plants. Anti-diabetes and Anti-obesity Medicinal Plants and Phytochemicals: Safety, Efficacy, and Action Mechanisms is a much-needed and truly original work, finally presenting in one place all the necessary information on medicinal plants used in conjunction with obesity and diabetes prevention.
Introduction to Diabetes and Obesity -- Introduction to Medicinal plant Safety and Efficacy -- Anti-Diabetic medicinal plants -- Anti-obesity medicinal plants -- Action mechanism of anti-diabetic medicinal plants -- Action mechanism of anti-obesity medicinal plants -- Anti-diabetic phytogenic natural products -- Anti-obesity phytogenic natural products -- Future trends of anti-diabetic andante-obesity medicinal plants.
Keywords: Food science; Pharmaceutical chemistry; Food Science; Pharmaceutics